2010 International Conference on Management and Service Science 2010
DOI: 10.1109/icmss.2010.5576113
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Double Generally Weighted Moving Average Control Chart for Individual Observations

Abstract: This study investigates control charts for simultaneous monitoring of process mean and process variability when an individual observation is taken at each sampling point. A combined scheme consisting of a two-side double generally weighted moving average (DGWMA) mean chart and a two-side DGWMA variance chart is developed. This new combined scheme will compare with the combined generally weighted moving average (GWMA) charts. It is shown that the combination of the DGWMA charts is more sensitive than the combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Sheu and Hsieh 35 studied the DGWMA control chart for the normal distribution, and it was found more effective than the DEWMA and GWMA control charts in detecting moderate shifts of the process mean. Other studies about the DGWMA control charts are Tai et al, 36 Sheu et al, 37 Huang et al, 38 Chiu and Lu, 39 Chiu, 40 and Lu. 41 In this article, a one-sided DGWMA control chart with a time-varying control limit based on gamma distribution is proposed for monitoring the TBE and detecting a downward shift in a process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sheu and Hsieh 35 studied the DGWMA control chart for the normal distribution, and it was found more effective than the DEWMA and GWMA control charts in detecting moderate shifts of the process mean. Other studies about the DGWMA control charts are Tai et al, 36 Sheu et al, 37 Huang et al, 38 Chiu and Lu, 39 Chiu, 40 and Lu. 41 In this article, a one-sided DGWMA control chart with a time-varying control limit based on gamma distribution is proposed for monitoring the TBE and detecting a downward shift in a process.…”
Section: Introductionmentioning
confidence: 99%
“…Sheu and Hsieh studied the DGWMA control chart for the normal distribution, and it was found more effective than the DEWMA and GWMA control charts in detecting moderate shifts of the process mean. Other studies about the DGWMA control charts are Tai et al, Sheu et al, Huang et al, Chiu and Lu, Chiu, and Lu …”
Section: Introductionmentioning
confidence: 99%
“…Tai et al 74 proposed a DGWMA (trueX¯&S2) scheme and showed that, in many situations, it has a better OOC ARL performance as compared to the corresponding GWMA (trueX¯&S2) scheme by Sheu et al 45 . Next, Huang et al 75 proposed a DGWMA SoS scheme and showed that it has a better ARL and SDRL detection ability than the corresponding DEWMA and GWMA SoS schemes in many situations.…”
Section: Dgwma Schemesmentioning
confidence: 99%
“…The IC design of the proposed DGWMA‐EX chart consists of obtaining the values for the charting constant, ie, L > 0 for chosen values of m (known as the reference sample size) and n (known as the test sample size) and a certain range of values for each ( q , α ) combination, so that the attained IC ARL is close to the desirable value ARL * which is typically 370 or 500. Sheu and Hsieh, Tai et al, and Huang et al noted that ( q , α ) combinations in the intervals 0.5 ≤ q ≤ 0.9 and 0.5 ≤ α ≤ 1.0 enhanced the sensitivity of the DGWMA‐ trueX¯ chart and outperformed the GWMA‐ trueX¯, DEWMA‐ trueX¯, and EWMA‐ trueX¯ charts for small shifts. Chakraborty et al considered m = 49 and 99 and n = 5 and 10 as the values for the reference sample and test sample sizes, respectively, and the following range of values for the GWMA‐EX parameters: q = 0.8, 0.9, 0.95 and α = 0.7, 0.8, 0.9, 1.0, 1.3.…”
Section: Implementation and Performancementioning
confidence: 99%
“…They have shown that the DGWMA‐ trueX¯ chart is more sensitive in detecting minor shifts in the process. The interested reader is referred to the works by Tai et al and Huang et al In typical applications, Shewhart‐type and time‐weighted charts are based on the fact that the observations of the underlying process are assumed to follow a normal or specified probability distribution. However, in many situations, the assumption of normality may not be justified or valid when the observations are from a non‐normal or unknown distribution.…”
Section: Introductionmentioning
confidence: 99%